EFFECTIVENESS OF MULLIGAN MOBILIZATION WITH CONVENTIONAL PHYSIOTHERAPY IN KNEE OSTEOARTHRITIS: - A CASE SERIES - S. JADHAV, VRUSHALI; ANAP, DEEPAK (International Journal of Clinical and Biomedical Research, 2015)
Background: Osteoarthritis (OA) is the most common joint disease causing disability. Current Physical therapy management for knee OA is aiming to increase range of motion and improve functional performance. So the purpose of this study to assess the effectiveness of Mulligan Mobilization along with Conventional Physiotherapy in Knee osteoarthritis patients. Method: Patients of knee pain who fulfilled inclusion criteria were taken in study. Outcome like The Knee Injury & osteoarthritis Outcome Score (KOOS) Index, ROM with the help of Universal Goniometer, Manual muscle testing with Medical Research Council (MRC) scale & time up and Go test were taken at baseline and after 4 wks. Mulligan Mobilization along with conventional Physiotherapy was given to all patients for 4 wks. Result: Showed there was significant improvement 25.08% in Koos Index, while in knee flexion ROM, improvement on right side was 9.94% or in left side 6.20%. while muscle strength in MMT with 25% on right side or 4% on left side improvement seen forÂ  knee flexor and 5% on right side or no any improvement seen on left side for knee extensor. Time up and go test also showed 10.89% improvement compared to baseline. Conclusion: Improvement is seen in patients with knee osteoarthritis by Mulligan Mobilization along with Conventional Physiotherapy.